2009
DOI: 10.1111/j.1440-1789.2008.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted human embryonic neural stem cells survive, migrate, differentiate and increase endogenous nestin expression in adult rat cortical peri‐infarction zone

Abstract: Transplantation of stem cells is a potential therapeutic strategy for stroke damage. The survival, migration, and differentiation of transplanted human embryonic neural stem cells in the acute post-ischemic environment were characterized and endogenous nestin expression after transplantation was investigated. Human embryonic neural stem cells obtained from the temporal lobe cortex were cultured and labeled with fluorescent 1,1'-dioctadecy-6,6'-di (4-sulfopheyl)-3,3,3',3'-tetramethylindocarbocyanin (DiI) in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…5A, images of cell death were detected with the TUNEL method. Transplantation of NSCs decreased cell death, compared to that observed in the model group, which was consistent with previous findings [1,27,28]. Notably, transplantation of NAAGS/NSCs suppressed cell death more significantly at 7 and 14 days after TBI, compared to NSC transplantation (Fig.…”
Section: Resultssupporting
confidence: 82%
“…5A, images of cell death were detected with the TUNEL method. Transplantation of NSCs decreased cell death, compared to that observed in the model group, which was consistent with previous findings [1,27,28]. Notably, transplantation of NAAGS/NSCs suppressed cell death more significantly at 7 and 14 days after TBI, compared to NSC transplantation (Fig.…”
Section: Resultssupporting
confidence: 82%
“…Recent study has also shown that in a rat model of cerebral infarction, NSC transplantation not only provided a more favorable microenvironment for endogenous NSC proliferation and cell death inhibition through paracrine pathways, but also promoted angiogenesis (Zhang et al, 2011). This may be related to the release of various nutritional factors from NSCs, such as epidermal growth factor, fibroblast growth factor, and VEGF (Zhang et al, 2009). As a highly specific multifunctional cytokine that affects the vascular endothelium, VEGF functions in endothelial cell apoptosis inhibition, promotion of angiogenesis, and neuroprotection to promote the repair of spinal cord injury (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Neural stem cells (NSC) are promising candidate cells for neural transplantation therapy and have been shown to promote functional recovery after spinal cord injury through cell and tissue replacement (Sandner et al, 2012). Recent studies have shown that NSCs can not only replace damaged nerve tissue, but also promote angiogenesis in the ischemic area of cerebral infarction (Zhang et al, 2009). These cells can also promote the expression of various growth factors through paracrine signaling pathways (Ii et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this transplanted NSCs managed to survive, migrate, differentiate, and also induce improvement in neurological functions (Zhang et al, 2009a(Zhang et al, , 2009bZhang et al, 2010). Grafted NSCs enhanced the number of BrdU-positive cells in ischemic ipsilateral SVZ at 7 days after transplantation, an effect that persisted to at least 14 days post-transplantation.…”
Section: From Theory To Practice: Nscs Transplant In Rodent Models Ofmentioning
confidence: 86%